2001
DOI: 10.1086/318424
|View full text |Cite
|
Sign up to set email alerts
|

First Stellar Abundances in NGC 6822 from VLT‐UVES and Keck‐HIRES Spectroscopy

Abstract: and was made possible by the generous financial support of the W. M. Keck Foundation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
146
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 52 publications
30
146
1
Order By: Relevance
“…The galaxy appears to have experienced a relatively steady rate of star formation over the last ∼11 Gyr, although there are signs of a recent increase (Clementini et al 2003;Komiyama et al 2003;Gallart et al 1996), and it has a large and well studied AGB population. NGC 6822 has been the subject of multiple studies to estimate its iron abundance (Venn et al 2001;Tolstoy et al 2001;Davidge 2003b;Clementini et al 2003;Kang et al 2006). Sibbons et al (2012; hereafter Paper I) estimated the global iron abundance of the AGB population of the galaxy from the calculated C/M ratio; using JHK photometry of a ∼3 deg 2 area centred on NGC 6822 (α(2000.0) = 19 h 44 m 56 s , δ(2000.0) = −14 • 48 06 ).…”
Section: Aims Of This Papermentioning
confidence: 99%
“…The galaxy appears to have experienced a relatively steady rate of star formation over the last ∼11 Gyr, although there are signs of a recent increase (Clementini et al 2003;Komiyama et al 2003;Gallart et al 1996), and it has a large and well studied AGB population. NGC 6822 has been the subject of multiple studies to estimate its iron abundance (Venn et al 2001;Tolstoy et al 2001;Davidge 2003b;Clementini et al 2003;Kang et al 2006). Sibbons et al (2012; hereafter Paper I) estimated the global iron abundance of the AGB population of the galaxy from the calculated C/M ratio; using JHK photometry of a ∼3 deg 2 area centred on NGC 6822 (α(2000.0) = 19 h 44 m 56 s , δ(2000.0) = −14 • 48 06 ).…”
Section: Aims Of This Papermentioning
confidence: 99%
“…From this we obtain 12 + log (O/H) = 8.16 ± 0.05. On the other hand, from A-type supergiant stars, Venn et al (2001) derived the chemical abundance of iron to be 12 + log (Fe/H) = 7.01 ± 0.20. These data will be used as observational constraints for the present component of the ISM.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…The present age of the galaxy is assumed to be 13.5 Gyr. In this table we also present the Fe/H value by Venn et al (2001) from A-type supergiants. Because most of the Fe in H ii regions and PNe is trapped in dust grains (Peimbert & Peimbert 2010;Shields 1978;Delgado-Inglada et al 2009), we do not present the gaseous Fe/H abundance.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…The galaxy is embedded in a large HI envelope (Weldrake et al 2003). Previous spectroscopic studies, although incomplete, of supergiants (Venn et al 2001), HII regions (Chandar et al 2000), and red giant branch (RGB) stars (Tolstoy et al 2001) found evidence of a gradient in [O/H] and measured an average [Fe/H] = −0.9 dex with a spread of 1.5 dex. Most importantly, this galaxy has a large and widely distributed intermediate-age population (Battinelli et al 2006) with a clear spread in metallicity (Cioni & Habing 2005).…”
Section: Introductionmentioning
confidence: 99%